Evaluation of Mean Apical Sealing Ability of Bio Ceramic and AH Plus (Dentsply Sirona) Sealer in Single Rooted Teeth: An In Vitro Study: Apical Sealing for Single Rooted Teeth - Memon, Jazib; Iqbal, Kanza; Mallick, Mariam Raza; Dehraj, Mohsin Ali; Ali, Ahsan; Kumar, Kelash (Pakistan Journal of Health Sciences, 2024)
A good seal is essential to prevent bacteria from re-entering the canal. Sealers can significantly impact the success of the treatment. Understanding which sealant works better can help dentists improve the outcome of root canal treatments. Objective: To compare mean apical sealing ability of bioceramic sealer and AH plus sealer in single rooted tooth. Methods: Extracted single-rooted teeth were divided into two groups and sealed with either bioceramic or AH plus sealer. After soaking in dye solution, the depth of dye penetration was measured to assess leakage. Results: Bioceramic sealer showed significantly better apical sealing ability (mean 5.43 mm) compared to AH plus (mean 8.55 mm), suggesting it may be a more effective choice for preventing future problems after root canal treatment. Conclusions: The study concluded that bioceramic sealer is superior to AH plus in sealing the tips of single-rooted teeth. This finding can help dentists choose the most effective sealant for their patients, potentially reducing the chance of treatment failure.